Are Firms Gerrymandered? - Joaquín Artés; Aaron Russell Kaufman; Brian Kelleher Richter; Jeffrey F. Timmons (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2022)
We provide the first evidence that firms, not just voters, are gerrymandered. We compare allocations of firms in enacted redistricting plans to counterfactual distributions constructed using simulation methods. We find that firms are over-allocated to districts held by the mapmakers' party when partisans control the redistricting process. Firms are more proportionately allocated by redistricting commissions. Our results hold when we account for the gerrymandering of seats: holding fixed the number of seats the mapmakers' party wins, firms tend to obtain more firms than expected. Our research reveals that partisan mapmakers target more than just voters.
Keywords: 330